2005
DOI: 10.1016/j.femsec.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

1-Octen-3-ol inhibits conidia germination of Penicillium paneum despite of mild effects on membrane permeability, respiration, intracellular pH, and changes the protein composition

Abstract: 1-Octen-3-ol is a volatile germination self-inhibitor produced by Penicillium paneum that blocks the germination process. The size of conidia treated with 1-octen-3-ol was similar to that of freshly harvested conidia. Exposure to 1-octen-3-ol resulted in staining of 10-20% of the conidia with PI and TOTO, fluorescent DNA probes that cannot enter cells with an intact membrane, whereas only 3-5% of non-treated conidia were stained. Addition of 1-octen-3-ol to germinating conidia resulted in transient dissipation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 32 publications
4
53
0
1
Order By: Relevance
“…The addition of 1-octen-3-ol to Penicillium paneum conidia results in a slight permeabilization of the plasma membrane and significantly alters protein expression (Chitarra et al, 2005). Changes in membrane permeability are known to accompany conidiation in Trichoderma but are not themselves sufficient to induce conidiation (Nemcovic et al, 2008).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…The addition of 1-octen-3-ol to Penicillium paneum conidia results in a slight permeabilization of the plasma membrane and significantly alters protein expression (Chitarra et al, 2005). Changes in membrane permeability are known to accompany conidiation in Trichoderma but are not themselves sufficient to induce conidiation (Nemcovic et al, 2008).…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…(N = 270) **P \ 0.01, ***P \ 0.001 postharvest storage of strawberry, blackberry, and grape [2]. Although it has not been used for postharvest control of pathogens, 1-octen-3-ol inhibits spore germination and induces microconidiation in Penicillium paneum [11,12]. The ability of eight-carbon volatiles to affect germination of conidia was also reported with Aspergillus nidulans [26] and Lecanicillium fungicola [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, under conditions of high spore density, 1-octen-3-ol functions as a self-inhibitor in Penicillium paneum and Agaricus bisporus [11,12,52]. Selfinhibitors inhibit spore germination reversibly, possibly through effects on the plasma membrane [12]. At certain concentrations, the eight-carbon oxylipins 1-octen-3-ol, 3-octanone, and 3-octanol stimulate aerial conidiation in Aspergillus nidulans [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galindo et al, 2004, well-described 6-pentyla-pyrone (6-PAP) as a volatile product of secondary metabolism and this compounds act as herbicide and antimicrobial. In addition to, Combet et al, 2006, was reported, eight carbon volatile compounds such as 1-octen-3-ol, 3-octanone, 3-octanol and 1-octen-3-one and these compounds are typical mushroom components and they play important role such as insect attractants, exhibit fungi-static and fungicidal effects (Chitarra et al, 2004;2005;Okull et al, 2003).…”
Section: International Journal Of Current Microbiology and Applied Scmentioning
confidence: 98%